FAKTOR FAKTOR YANG MEMENGARUHI FIRM VALUE - Siauhelung, Leonard Hizkia; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to obtain empirical evidence about the effect of capital structure, profitability, liquidity, activity ratio, and firm size towards firm value on manufacturing companies listed on the Indonesian Stock Exchange during the 2018-2021 period. The research design used in this research is descriptive research with purposive sampling method and 304 data were collected. This study uses the Eviews 12 Student Version Lite application for data processing. The result shown in this study are that capital structure dan profitability have a positive effect on firm value, firm size has a negative effect on firm value, while liquidity and activity ratio have no positive effect on firm value. The implication of this study is that companies need to pay attention to capital structure, profitability, and firm size to maximize the company's value.